ANALISIS KINERJA KEUANGAN DAN HARGA SAHAM PERBANKAN DI BURSA EFEK INDONESIA (BEI) - - Wijayanti (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2010)
This research was aimed at searching the anwer for question whether financial achievement of firm really affected the price of its stock or the speculative activites were the main sources for stock price fluctuation. Financial performance was shown by some fundamental indicators such as CAR, ROA, NIM, NPL, LDR, EPS, and PER, while speculation often look over the historical pattern of stock prices in thepast which indicated by P1 and P2. Regression was used as the tools for analyzing the problem. Data were collected from all banks listed in BEJ in 2005. The research found that overall, all variables had significant impact on stock prices, but not all individual variable had the same role. Variables: ROA, NIM, EPS, PER, and P1 were individually had significant impact on the stock price while CAR, NPL, LDR and P2 did not. Thus, author concluded that beside financial indicators could influence people to buy and sell their stock, the stock price was also still significantly affected by the action of speculants.Keywords: financial achievement, speculation, banks, stock price.